Materials Science and Technology 2012
DOI: 10.1002/9783527603978.mst0415
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Polymerization: Recent Advances

Abstract: polymerize the monomers in classes B, C, and D, but they cannot initiate the polymerization of monomers in class A. The initiators in class c can polymerize both C and D class monomers, while they are inert for the monomers in classes A and B. The least-reactive initiators in class d, such as amines and phosphines, undergo anionic polymerization of the most-reactive D class monomers Among the monomers, α-cyanoacrylate is polymerized, even with water.The relationship between a monomer and its growing chain-end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 293 publications
(225 reference statements)
0
15
0
Order By: Relevance
“…Second, extremely narrow molecular weight distributions are attained, M w /M n values being 1.05 or even smaller. Third, the tolerance of various functional groups, much more than the numbers that one can consider, can be realized, although some of them are required to be protected during polymerization [28][29][30][31][32][33]. Finally, the resulting living anionic polymers have active chain-end anions that are highly reactive, but stable under appropriate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Second, extremely narrow molecular weight distributions are attained, M w /M n values being 1.05 or even smaller. Third, the tolerance of various functional groups, much more than the numbers that one can consider, can be realized, although some of them are required to be protected during polymerization [28][29][30][31][32][33]. Finally, the resulting living anionic polymers have active chain-end anions that are highly reactive, but stable under appropriate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the relative anionic polymerizability (electrophilicity) of the above vinyl monomers, categories (i) and (ii), is well related to the relative reactivity (nucleophilicity or basicity) of anionic initiators. It has been reported that vinyl monomers are categorized into four classes, (A)-(D) ( Table 1) [2]. Conjugated hydrocarbons, such as styrene and 1,3-diene monomers, correspond to the least reactive monomers under the anionic conditions in class (A).…”
Section: Fundamentals Of Anionic Addition Polymerization Monomersmentioning
confidence: 99%
“…Among these living polymerization systems, this living anionic addition polymerization of hydrocarbon monomers, such as styrene and 1,3-dienes, is still a most established system and allows a synthesis of well-defined polymers possessing predicted molecular weights and narrow molecular weight distributions. Furthermore, the living character of the propagating carbanion enables to prepare the tailored block copolymers by the sequential copolymerization and the end-functionalized polymers by the suitable termination reactions [1][2][3] (Fig. 10).…”
Section: Living Anionic Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Living anionic polymerization provides the best and the most elegant method for preparing block copolymers by the sequential addition of different monomers because it can produce block copolymers in which each block has a predictable molecular weight in a wide range and a very narrow molecular weight distribution under the adequate reaction conditions [1,2]. A variety of vinyl monomers, such as styrene derivatives, 1,3-dienes, alkyl methacrylates, and acrylamides, are capable of living anionic polymerization.…”
Section: Synthesis Of Block Copolymers By Sequential Living Polymerizmentioning
confidence: 99%